Modelling of the effect of centrifugal forces on bearings in planet gear mechanism of a yarn twisting machine - Karagöz, Kaan (My University, 2005)
MODELLING OF THE EFFECT OF CENTRIFUGAL FORCES ON BEARINGS IN PLANETARY GEAR MECHANISM OF A YARN TWISTING MACHINE Planet dişli mekanizmaları güç iletimi sistemleri arasında en yaygın olanlarından birisidir. Otomobillerin modern otomatik vites sistemlerinden robotikte kullanılan servomotorların hız düşürücü mekanizmalarına kadar varan geniş bir kullanım alanları vardır. Planet dişli mekanizmaları için bir yeni kullanım alanı da tekstil endüstrisi için geliştirilmiş olan yeni nesil bir iplik büküm makinesidir. Ancak uydusal yörüngede çalışan rulmanların arızalanmasından dolayı, bu mekanizmanın makine üzerindeki ömrü uzun olamamaktadır. Bu tezin amacı bu mekanizmanın rulmanlardan kaynaklanan arıza sebeplerini araştırmak ve merkezkaç kuvvetlerin bilyalı rulmanlar üzerindeki etkilerini incelemektir. Bu çalışmada elde edilen deneysel sonuçlar teorik çalışmalar ve literatürdeki bilgilerle uyumlu sonuçlar vermiştir. Merkezkaç kuvvetin rulmanların bilyalarına olan etkisinin, rulmanların iç bileziğinin dış bileziğine göre olan yer değiştirmesini arttırdığı sonucuna varılmıştır. Buna ek olarak merkezkaç kuvvetin rulmanların kafesine olan etkisinin daha detaylı çalışılması gerekmektedir. MODELLING OF THE EFFECT OF CENTRIFUGAL FORCES ON BEARINGS IN PLANETARY GEAR MECHANISM OF A YARN TWISTING MACHINE One of the most common power transmission systems is the planetary gear mechanism. It is used in a very wide range of applications from modern automatic transmission systems of automobiles to speed reduction mechanisms in servomotors used in robotics. One new application field for the planetary gear mechanisms is a new generation yarn-twisting machine for the textile industry. But the life of the mechanism on this machine is not satisfactory due to the failure of the bearings, which operate planetary. The purpose of this thesis is to investigate the reasons of failure of this system because of the bearings and to understand the effects of centrifugal forces on ball bearings. In this study the experimental work agree with the theoretical work and the data available in literature. It is found out that the effect of centrifugal forces on the balls of the bearings increases the relative radial displacement of the inner rings of bearings with respect to their outer rings. In addition, the effect of centrifugal forces on bearing cages needs to be studied further.
Keywords: Makine Mühendisliği; Makine Mühendisliği2005